State laws on tobacco control -- United States, 1998. - Fishman JA; Allison H; Knowles SB; Fishburn BA; Woollery TA; Marx WT; Shelton DM; Husten CG; Eriksen MP (MMWR: Morbidity & Mortality Weekly Report)
Problem/Condition: Cases of work-related asthma (WRA) are sentinel health events that indicate the need for preventive intervention. WRA includes new-onset asthma caused by workplace exposure to sensitizers or irritants and preexisting asthma exacerbated by workplace exposures. Reporting Period: This report reviews cases of WRA identified by state health departments from January 1, 1993, through December 31, 1995, as well as follow-up investigations of cases and associated workplaces conducted through June 30, 1998. Description of the Systems: State-based surveillance and intervention programs for WRA are conducted in California, Massachusetts, Michigan, and New Jersey as part of the Sentinel Event Notification Systems for Occupational Risks (SENSOR) cooperative agreement program, initiated by CDC's National Institute for Occupational Safety and Health (NIOSH). Results: From 1993 through 1995, a total of 1,101 cases of WRA were identified by SENSOR surveillance staff members in California, Massachusetts, Michigan, and New Jersey. Of these 1,101 cases, 19.1% were classified as work-aggravated asthma, and 80.9% were classified as new-onset asthma. Objective evidence substantiating asthma work-relatedness was documented in the medical records of 3.4% of WRA cases identified in the two states (Michigan and New Jersey) where medical records are routinely reviewed for this information. Indoor air pollutants, dusts, cleaning materials, lubricants (e.g., metalworking fluids), and diisocyanates were among the most frequently reported causes of WRA. In addition, a well-recognized cause of occupational asthma - natural rubber latex - was identified in a new setting, the health-care industry. The most common industries associated with WRA cases included transportation equipment manufacturing (19.3%), health services (14.2%), and educational services (8.7%). Air sampling for agents known to induce occupational asthma was performed in Michigan for comparison with established federal time-weighted average exposure limits. Sixteen (13.4%) of 119 workplaces tested had airborne concentrations exceeding NIOSH recommended exposure limits (RELs); 11 (9.1%) of 121 workplaces had concentrations exceeding permissible exposure limits (PELs) of the Michigan Occupational Safety and Health Act (MIOSHA) program.* Interpretation: The surveillance data findings confirm well-recognized causes of asthma and have identified new putative causes (e.g., cleaning materials and metal-working fluids). Because the surveillance program depends on physicians' recognizing asthma work-relatedness and reporting diagnosed cases, the data are considered an underestimate of the magnitude of the WRA problem. The data also indicate that physicians are not commonly performing objective physiologic tests to substantiate a WRA diagnosis. Workplace findings suggest a need to evaluate existing exposure standards for specific agents known to induce occupational asthma (e.g., diisocyanates). Case-based surveillance can help improve the recognition, control, and prevention of WRA. The SENSOR model also provides a mechanism for workers and physicians to request workplace investigations aimed at primary prevention for other workers. Public Health Action: NIOSH and state health department representatives are working to establish a long-term agenda for state-based surveillance of work-related conditions and hazards. The results from the SENSOR WRA programs described in this report support inclusion of WRA as a priority condition warranting surveillance at the state level.